Moving away from the “Repression-Resistance” Paradigm: The Effects of Civil/Uncivil Disagreements on Political Deliberation in China - Guan, Tianru; Chen, Xiaotong (Javnost-The Public, 2023)
This study engages in the academic effort of moving beyond the “repression-resistance” lens by shedding light on the civic function of exposure to cross-cutting arguments and their (in-) civility on individual’s expression willingness and discursive quality in China’s cyberspace. While civility and dissonant-viewpoint exposure are viewed as the hallmark of political deliberation and public sphere in most Western societies, whether their potential could be realised in a censored yet increasingly pluralist media space in China remains a question. Through experiment method (N = 1064), participants were exposed to dissonant (civil/uncivil) viewpoints that were selected, manipulated, and presented as original Weibo posts, regarding a controversial marital policy. Our results illustrate that exposure to civil yet reasoned cross-cutting information significantly provokes individuals’ willingness to engage in a manner of reciprocal civility. Implications are discussed for deliberation studies and internet governance.